PENGEMBANGAN MEDIA PEMBELAJARAN SCRAPBOOK MATERI KERAGAMAN BUDAYA INDONESIA KELAS IV UPT SD NEGERI SUKOREJO 03 - Khonik Rokimah; Shofi Nur Amalia; Widyarnes Niwangtika (Jurnal Manajemen Pendidikan, 2026)
This study aims to develop a teaching resource scrapbook for the Pancasila Education subject in fourth-grade elementary school that covers cultural diversity in Indonesia, specifically focusing on diverse traditional homes, clothing, weapons, food, and art. This study implements a Research and Development (R&D) perspective through the ADDIE model, which consists of five steps: analysis, design, development, implementation, and evaluation. Content validation by experts yielded a score of 90%, classified as “Highly Valid”; media validation by experts recorded a score of 96%, classified as “Highly Valid”; the language evaluation by experts yielded a score of 95%, classified as “Highly Valid”; and the practicality evaluation by classroom teachers yielded a score of 94%, classified as “Highly Valid.” The effectiveness of the instructional media was evaluated through pretest and posttest analysis. Based on the pretest and posttest results and the N-Gain calculation, a value of 0.75 was obtained. According to the table, g > 0.70 falls into the “high” category. This value falls within the 56–75% range, categorized as “moderately effective.” It can be concluded that the scrapbook learning media designed for Pancasila Education lessons on the topic of Indonesia’s cultural diversity is effective for use by students in Grade 4 at UPT SD Negeri Sukorejo 03.